2018
DOI: 10.1139/apnm-2017-0468
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hepatic gene expression profiles by vitamin B1, vitamin B2, and niacin supplementation in mice exposed to acute hypoxia

Abstract: This study was aimed to observe the effects of vitamin B, vitamin B, and niacin supplementation on hepatic gene expression profiles in mice exposed to acute hypoxia. Thirty mice were randomly divided into normal, acute hypoxia, and acute hypoxia plus vitamin B, vitamin B, and niacin supplementation groups and fed corresponding diets for 2 weeks and then exposed to a simulated altitude of 6000 m for 8 h. Hepatic gene expression profiles were analyzed using a microarray technique. Several biochemical markers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Melatonin (MT) (Claustrat and Leston, 2015), which reduces the release of excitatory amino acids and which was significantly decreased in the body of the hypoxia group, further mediates the accumulation and neurotoxicity of excitatory amino acids and may even induce the occurrence of high-altitude cerebral edema (Ruan et al, 2000;Zhu and Xu, 2019). It is worth noting that a large number of B vitamins can reduce disorders of amino acid metabolism caused by hypoxia and that appropriate supplementation of vitamin B (VB) may play a certain role against hypoxic injury in the body (Liu et al, 2018). Our metabolome data results showed that VB2 in rat venous blood decreased significantly in HAPE, suggesting that VB2 levels may decrease exhaustively in a hypoxic environment.…”
Section: Three Major Nutrientsmentioning
confidence: 74%
See 1 more Smart Citation
“…Melatonin (MT) (Claustrat and Leston, 2015), which reduces the release of excitatory amino acids and which was significantly decreased in the body of the hypoxia group, further mediates the accumulation and neurotoxicity of excitatory amino acids and may even induce the occurrence of high-altitude cerebral edema (Ruan et al, 2000;Zhu and Xu, 2019). It is worth noting that a large number of B vitamins can reduce disorders of amino acid metabolism caused by hypoxia and that appropriate supplementation of vitamin B (VB) may play a certain role against hypoxic injury in the body (Liu et al, 2018). Our metabolome data results showed that VB2 in rat venous blood decreased significantly in HAPE, suggesting that VB2 levels may decrease exhaustively in a hypoxic environment.…”
Section: Three Major Nutrientsmentioning
confidence: 74%
“…It is worth noting that a large number of B vitamins can reduce disorders of amino acid metabolism caused by hypoxia and that appropriate supplementation of vitamin B (VB) may play a certain role against hypoxic injury in the body ( Liu et al, 2018 ). Our metabolome data results showed that VB2 in rat venous blood decreased significantly in HAPE, suggesting that VB2 levels may decrease exhaustively in a hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Using CRISPR–Cas9 gene editing, a point mutation knock-in mouse (Slc52a3P258L) was generated that showed higher riboflavin concentrations and downregulation of a number of lipid-associated metabolites in brain tissue, consistent with hyperlipidemia in the livers of Slc52a3 knockout mice ( 11 ). Of note, however, under exposure to chronic intermittent hypoxia, no metabolic changes were seen between wild-type and Slc52a3P258L mice, despite prior gene changes observed under acute hypoxia that were partially rescued with supplements including riboflavin ( 9 ).…”
mentioning
confidence: 97%
“…There are multiple potential mechanisms in which riboflavin deficiency could impact OSA. Additional riboflavin appears to be required under acute hypoxic conditions ( 9 ). Riboflavin is the precursor of flavin adenine dinucleotide, a coenzyme that affects HIF1A stability ( 10 ).…”
mentioning
confidence: 99%